Trauma and Recovery in the Twenty-Century Irish Novel - Bolfarine, Mariana (ABEI Journal, 2019)
Costello-Sullivan, Kathleen, Trauma and Recovery in the Twenty-Century Irish Novel. Syracuse: Syracuse University Press, 2018.